Social comparisons in ultimatum bargaining - Iris Bohnet; Richard Zeckhauser (Center for Research in Economics, Management and the Arts (CREMA), 2004)
This paper employs experiments to examine the effects of social comparisons in ultimatum bargaining. We inform responders on the average offer before they decide whether to accept or reject their specific offer. To provide a metric for social comparison effects, we compare them with another change in informational conditions, asymmetric information on the pie size. Knowing comparable offers or knowing the pie size increases offers and rejection probabilities by similar magnitudes. Our results are consistent with people disliking deviations from the norm of equity but inconsistent with fairness theories, where people dislike income disparity between themselves and their referents.
Keywords: C91; 330; Experimental bargaining; social comparisons; asymmetric information; ultimatum game